Perancangan Media Pembelajaran Interaktif Berbasis Augmented Reality Pada SD Al-Mukhlisin Berbasis Android - Hermayanti Hermayanti; Mufida Khairani; Rismayanti Rismayanti (Universitas Muhammadiyah Enrekang, 2023)
Learning media is anything that is used to convey messages or information in the teaching and learning process so that it can stimulate students' attention and interest in learning. Increasing the development of information and communication technology can have a positive impact on the education sector. Augmented Reality is part of the learning media that can be used to attract students' interest in learning. Augmented Reality has the advantage of being able to help improve student learning activities, simplify complex learning material, and present learning material practically. Insect animals (insecta) come from the Latin word insectum, which means cut into several parts, one of the classes of invertebrates in the phylum arthropods which have chitinous exoskeletons. The results of Augmented Reality learning media are that students are increasingly motivated to actively participate in learning activities, teachers can easily provide learning to motivate student